Penentuan Interval Waktu Penggantian Optimal Komponen Berdasarkan Model Opportunity Based-Age Replacement - Giatman, Muhammad (Sainstek, 2008)
Maintenance system, especially replacement that is not good, can cause much lose out for the company. The lose out is caused production process disturbing bay unexpectadly or unscheduled replacement. This will lose out for factory that have continue flow shop type, because replacement of the component that is need shut down machine will cause all machine in the process production stop. To anticipate of lose out that cause by replacement activity, so in this research will search interval of optimal time replacement that is can minimizing total cost of replacement especially for Bearing Pinger component in machine washer by using Opportunity Based-Age Replacement model. In Opportunity Based-Age Replacement model, Bearing Pinger will change before age-economic has done by using firs opportunity that is coming. The opprtunity is shut down production that has scheduled by PPIC department, and component replacement that have done in this opportunity not causing lose out because production process that stop expectadly. From the resul the manner of data has got total cost of replacement per hours that is leaved by Opportunity Base-Age Replacement model is smaller than total cost of replacement per hours by replacement bases on failure component that now is applied in PT. Coca Cola Bottling Indonesia-Central Sumatera. So, we get the conclusion that total cost of replacement for Bearing PingerÂ  of the company has decrease by using Opportunity Based-Age Replacement model. Keywords: Replacement, Optimal, Opportunity based age replacement, Preventive maintenance, Corrective maintenance.